Immobilized invertase - Kotwal, S. M.; Shankar, V. (Biotechnology Advances, 2009)
Invertase is a commercially important enzyme used for the hydrolysis of sucrose. The hydrolysis of sucrose yields an equimolar mixture of glucose and fructose, known as invert syrup, is widely used in food and beverage industries. This enzyme is also used for the manufacture of artificial honey, plasticizing agents used in cosmetics, pharmaceutical and paper industries as well as enzyme electrodes for the detection of sucrose. Immobilization of invertase and its biotechnological applications are reviewed. (c) 2009 Elsevier Inc. All rights reserved.
Keywords: Applications; Immobilization; Invert syrup; Saccharase

Streptomyces nucleases - Joshi, Amruta Pramod; Deshmukh, Sumedha Sharad (Critical Reviews in Microbiology, 2011)
Streptomyces nucleases are widely distributed and multifunctional enzymes acting on both DNA and RNA. They occur extra as well as intracellularly and can be classified under sugar specific and sugar non-specific nucleases. Nucleases play different roles like analytical, biological, and nutritional. They are also used in programmed cell death. Although more than 20 nucleases are reported to date, very little information is available regarding their structure-function relationship, active site based sequence homology, and the probable mechanism of action. This review describes the history, occurrence, localization, production, purification, properties, and applications of Streptomyces nucleases.
Keywords: Applications; Endonuclease; extracellular; production; Purification; Substrate specificity

Recent applications of starch derivatives in nanodrug delivery - Rodrigues, Asha; Emeje, Martins (Carbohydrate Polymers, 2012)
Starch has found use in industries as diverse as food, textiles, cosmetics, plastics, adhesives, paper, and pharmaceuticals. From a pharmaceutical standpoint, starch finds its value in solid-oral dosage forms, where it has been used as a binder, diluent, and disintegrant. However, only recently has the use of starch in nanotechnology started to make significant advances in biomedical applications, including newer drug delivery techniques. There has been a considerable effort to develop biodegradable nanoparticles as effective drug delivery systems. Being cheap, non-toxic, renewable, biodegradable and compatible with many other materials for industrial applications, starch is attracting the interest of drug delivery scientists. We have put together in a short and concise format, recent applications of starch derivatives in the emerging field of nanodrug delivery with the conclusion that a lot still needs to be done. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Applications; nanotechnology; Starch

Poly(2,5-Benzimidazole)-based flat sheet membranes: investigating effects of dope solvent and membrane heat treatment on forward osmosis and acid enrichment performances - Somkuwar, Nitin C.; Thorat, Nitin M.; Ambade, Ashootosh; Kharul, Ulhas K. (Journal of Applied Polymer Science, 2026)
The present work investigates two methods for preparing defect-free, symmetric membranes of the thermochemically robust polymer, poly(2,5-benzimidazole) (commonly known as ABPBI) for forward osmosis (FO), a growing technology for niche separations. The obtained polymer and membranes were analyzed for physical properties of significance. The FO analysis was performed using three salt solutions, viz., sodium chloride (NaCl), magnesium chloride (MgCl2), and sodium sulfate (Na2SO4). The effects of casting methodology (solvents present in the dope), membrane heat treatment, draw solution concentration, long-duration analysis, and FO-assisted enrichment of organic acids were evaluated. Some of the membranes exhibited extremely low reverse salt flux (RSF), which conveys the novelty of these membranes. Some of these membranes were analyzed using a high draw solution (DS) concentration (4 mol L-1) to enhance water flux and further employed to enrich organic acids. The aqueous acetic and methacrylic acid concentrations were enriched from 4.89 and 2.93 mol L-1 to 11.88 and 10.01 mol L-1, respectively. These results demonstrate an unmet need of concentrating methacrylic acid (a temperature-sensitive compound possessing a double bond). The present work demonstrates the potentials of ABPBI-based symmetric, thin membranes for FO and their industrial applicability for the first time.
Keywords: Applications; membranes; separation techniques